2017
DOI: 10.1007/s11605-017-3362-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Visceral Obesity and Postoperative Colon Cancer Outcomes

Abstract: Background Quantitative computed tomography (CT) assessment of visceral adiposity may be superior to body mass index (BMI) as a predictor of surgical morbidity. We sought to examine the association of CT measures of obesity and BMI with short-term post-operative outcomes in colon cancer patients. Methods In this retrospective study, 110 patients treated with colectomy for Stage I–III colon cancer were classified as obese or non-obese by pre-operative CT-based measures of adiposity or BMI. [Obese: BMI≥30kg/m2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 49 publications
2
54
1
Order By: Relevance
“…There was no significant difference in tumour location and surgical approach between the obese group and the non‐obese group, excluding the influence of such interference factors. Among the three obesity indicators (BMI, V/S, VFA), only higher VFA was associated with elevated risk of complications, which was consistent with the study performed at the Moffitt Cancer Center . Findings about BMI's value in predicting surgical outcomes are often contradictive and inconclusive, which may due to the limitation that BMI does not account for the specific distribution of body fat.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…There was no significant difference in tumour location and surgical approach between the obese group and the non‐obese group, excluding the influence of such interference factors. Among the three obesity indicators (BMI, V/S, VFA), only higher VFA was associated with elevated risk of complications, which was consistent with the study performed at the Moffitt Cancer Center . Findings about BMI's value in predicting surgical outcomes are often contradictive and inconclusive, which may due to the limitation that BMI does not account for the specific distribution of body fat.…”
Section: Discussionsupporting
confidence: 80%
“…Commonly used measurements for visceral obesity includes VFA and V/S. VFA ≥100 cm 2 or V/S ≥0.4 is selected to define visceral obesity . About 107 patients were classified as obese or non‐obese by BMI, V/S and VFA, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tanaka et al [18] reported that Japanese have lower BMIs than Caucasians, though Japanese have a significantly greater amount of abdominal visceral fat compared with Caucasians after adjusting for age, sex, and abdominal subcutaneous fat. There have been reports that visceral obesity is a more accurate predictor of perioperative complications than BMI in patients with colon cancer, and patients classified as obese by visceral fat area had significantly higher incidence and overall complication rates compared with nonobese patients [19,20]. Visceral fat has been reported to be a predictive factor for postoperative complications in CD [21].…”
Section: Discussionmentioning
confidence: 99%